Comparative Analysis of Inquisitiveness Development Dynamics in Youths and Young Girls - I B Kudinova; S S Kudinov; N V Bogomazova (Peoples' Friendship University of Russia (RUDN University), 2012)
The empirical results of the longitudinal research of inquisitiveness in youths and young girls during their higher school study are presented in the article. The inquisitiveness research is done in the frame of A.I. Krupnov's conceptual approach. The comparison of the results is based on the factor analysis.